FROM “OPEN DOOR POLICY” TO MIGRANT CRISIS: THE REFORMING OF MIGRATION POLICY IN EUROPEAN AND NATIONAL DIMENSIONS (THE EXAMPLES OF GREAT BRITAIN AND FRANCE) - N. V. Eremina; A. Yu. Chikhachev (Сравнительная политика, 2016)
This article concentrates on the main problems of reforming of the current EU migration policy. The authors examine the EU’s legal norms and national judicial basics in the sphere in order to emphasize a certain evolution of the approaches of member states to migration control issues. Longterm crisis in the EU migration policies, which was strengthen in 2014-2015, is going ahead. National governments are obliged to seek for comprehensible ways out of such situation both at supranational and national levels. Hence, we can consider common features of their policies as well as evident distinctions. To illustrate last changes in European migration policy we use the examples of Great Britain and France. Both countries are concerned by huge diffi culties of their policy realization: the newcomers do not succeed to integrate themselves into society and prefer to live in isolated quarters with their culture and religion; at the same time, the popularity of radical anti-immigrant parties steadily grows. British and French governments are to fi nd a balance between free immigration policy and the duty to ensure security whereas security risks are rising in such social circumstances. The authors conclude that refugee crisis of 2014-2015 should induce European countries to rethink their migration policies. The «open door policy» and streams of refugees cause the overexertion of state’s potential to accommodate newcomers. The problem has already got a security dimension, so that more determined measures are necessary to be taken. British, French and other European governments should reestablish their priorities in favor of responsible and restrictive approach.